Origin of modern syphilis and emergence of a pandemic Treponema pallidum cluster - Arora, Natasha; Schuenemann, Verena J; Jäger, Günter; Peltzer, Alexander; Seitz, Alexander; Herbig, Alexander; Strouhal, Michal; Grillová, Linda; Sánchez-Busó, Leonor; Kühnert, Denise; Bos, Kirsten I; Davis, Leyla Rivero; et al. (Nature microbiology, 2016)
The abrupt onslaught of the syphilis pandemic that started in the late fifteenth century established this devastating infectious disease as one of the most feared in human history1. Surprisingly, despite the availability of effective antibiotic treatment since the mid-twentieth century, this bacterial infection, which is caused by Treponema pallidum subsp. pallidum (TPA), has been re-emerging globally in the last few decades with an estimated 10.6 million cases in 2008 (ref. 2). Although resistance to penicillin has not yet been identified, an increasing number of strains fail to respond to the second-line antibiotic azithromycin3. Little is known about the genetic patterns in current infections or the evolutionary origins of the disease due to the low quantities of treponemal DNA in clinical samples and difficulties in cultivating the pathogen4. Here, we used DNA capture and whole-genome sequencing to successfully interrogate genome-wide variation from syphilis patient specimens, combined with laboratory samples of TPA and two other subspecies. Phylogenetic comparisons based on the sequenced genomes indicate that the TPA strains examined share a common ancestor after the fifteenth century, within the early modern era. Moreover, most contemporary strains are azithromycin-resistant and are members of a globally dominant cluster, named here as SS14-Ω. The cluster diversified from a common ancestor in the mid-twentieth century subsequent to the discovery of antibiotics. Its recent phylogenetic divergence and global presence point to the emergence of a pandemic strain cluster.
Keywords: Genotype; DNA bakterií; Azithromycin; Global Health; celosvětové zdraví; DNA, Bacterial; lidé; genotyp; syfilis; Anti-Bacterial Agents; Genome, Bacterial; Evolution, Molecular; molekulární evoluce; bakteriální léková rezistence; genom bakteriální; azithromycin; pandemie; Genetic Variation; Phylogeny; Molecular Epidemiology; Sequence Analysis, DNA; Syphilis; Treponema pallidum; sekvenční analýza DNA; antibakteriální látky; fylogeneze; genetická variace; Drug Resistance, Bacterial; Pandemics; molekulární epidemiologie; Humans